ARTIFICIAL INTELLIGENCE IN MATHEMATICS LEARNING: A LITERATURE STUDY ON EDUCATIONAL TRANSFORMATION IN THE DIGITAL ERA - Syahrul Syawal; Fuji Gatraningrum; Milda Sari; Irmasuriani (Journal Informatic, Education and Management (JIEM), 2026)
Artificial Intelligence (AI) has fundamentally transformed the landscape of mathematics learning in the digital era. This study aims to: (1) map the trends and development of AI application in mathematics learning, (2) analyze the effectiveness of AI in improving student learning outcomes and motivation, and (3) identify the challenges and opportunities of AI implementation in the context of Indonesian mathematics education. The method employed is a literature study through searches of various reputable scientific databases. The findings reveal that AI platforms such as Photomath, ChatGPT, and Socratic dominate utilization in mathematics learning. Their effectiveness is evidenced by a 20.6% improvement in students' mathematics scores and an 84.6% increase in teacher competence. However, student dependence on AI, infrastructure limitations, and low digital literacy remain primary obstacles. This study concludes that planned, ethical, and policy-based AI integration is crucial for realizing adaptive, inclusive, and high-quality mathematics learning in the era of digital transformation.